Pengaruh Waktu Ekstraksi, Rasio Bahan/Pelarut, dan Daya Microwave Terhadap Hasil Ekstraksi Minyak Serai Dapur dengan Bantuan Gelombang Mikro - Augustia, Venitalitya A. S.; Charfadz, Naufal; Akbar, Rizki; Diana (Jurnal Teknik Kimia USU, 2021)
Lemongrass, one type of source of essential oils, is widely cultivated in Indonesia. There are several methods for extracting the essential oils from lemongrasses, such as hydro-distillation, steam distillation, soxhlet extraction, extraction with supercritical fluids, ultrasonic extraction, and microwave-assisted hydro-distillation. In this study, microwave-assisted hydro-distillation was used as the extraction method. The purpose of this study was to determine the effect of extraction time (60 minutes, 75 minutes, and 90 minutes), lemongrass/solvent ratio (1:4 g/mL and 1:5 g/mL), and microwave power (500 watt and 600 watt) on quantity and quality of lemongrass essential oil. The essential oils obtained were analyzed in the form of calculation of the essential oil density, yield, and GC-MS analysis. The results of the analysis showed that the density of the extracted lemongrass oil ranged from 0.880 g/mL – 0.920 g/mL at a temperature of 30 oC, with the highest yield ranging from 0.0044% – 0.0046% in samples with a material/solvent ratio of 1:5 g/mL. The components found in lemongrass oil were Z-citral, geranyl acetate, geraniol.